Cacao grafting increases crop yield without compromising biodiversity - Ocampo-Ariza, Carolina; Müller, Sophie; Yovera, Fredy; Thomas, Evert; Vansynghel, Justine; Maas, Bea; Steffan-Dewenter, Ingolf; Tscharntke, Teja (Wiley, 2025)
Yields of tropical tree crops decline with time, often forcing smallholders to establish new deforestation‐derived plantations. Consequently, alternative strategies reconciling crop yield and biodiversity conservation are essential. Grafting is a common propagation method to boost yield in crops as cacao, but it alters tree structure potentially affecting associated insect diversity. We investigated how grafting affects cacao yield and biodiversity, modulated by local management and landscape, that is shade‐tree cover and distance to nearest forest. Within nine organic agroforests in Peru, we monitored the number of pods yielded over 2 years by ~190 trees per plot, and compared production levels with non‐grafted trees. We collected arthropods on 54 trees shortly after grafting and replicated surveys in the dry and rainy season, with standardized diurnal and nocturnal inspection of tree branches. We expected grafting would increase yield after a brief gap, while the arthropod community associated with freshly grafted cacao would differ from that of full‐grown cacao trees. Cacao grafting increased yields after 2 years by an average of 45% more than adjacent non‐grafted trees. Compared to non‐grafted trees, arthropod abundance was 25% lower 3 months after grafting and 12% lower after 6 months, indicating a recovery of arthropod communities shortly after grafting. Similar patterns were observed for species richness (22% and 12%) and Hill–Shannon diversity (18% and 13%). Abundance of phytophagous insects (mainly aphids) was unchanged with grafting. However, we found 46% fewer beetles and 39% fewer predatory arthropods (mainly spiders) on young—but not old—grafted cacao, indicating a possible decrease in pest control services by predatory arthropods at early grafting stages. We observed richer, more diverse, but less abundant arthropods during nocturnal surveys than on diurnal surveys. Arthropods were richer, more abundant and diverse in the rainy season than in the dry season. Increasing shade‐tree cover decreased arthropod diversity but did not affect species richness or abundance. Shorter distances from forest decreased richness and diversity, but not abundance, possibly due to higher pressure from vertebrate predators nearby forests. Synthesis and applications . Grafting is a successful approach for rejuvenating old, unproductive cacao trees, enhancing smallholder income opportunities and thus reducing pressure for new deforestation‐based plantations. Grafting briefly reduced arthropod abundance and diversity, but recovered in a short time. Hence, rejuvenation of cacao trees by grafting should be promoted and implemented as a promising strategy for more sustainable social‐ecological cacao management, with economic and ecological benefits for smallholders.